An Appraisal of Financial Authority Transfers' Prior-Knowledge in Adult Learning Assessment - A. Ettien; A. N'Guessan; B. N'Guetta (University of Sofia, 2017)
This research aimed at reviewing financial authority trainers prior knowledge in adult learners' learning assessment. For this aim, we tried to verify the fol-lowing research hypothesis: Ivorian financial authority trainers are able to assess adult learners correctly. Knowles andragogy principles are the comparison basis. We were positively impressed by trainers awareness of some of the principles of andragogy relative to their avoidance of summative assessment in favor of task-based assessment and problem-solving activities. However, the same trainers tendency to ignore the self-directedness nature of adult learners as well as their ability to engage in self-assessment made us believe that a sound training in adult learning assessment would help each of them become a better adult trainer.